2019
DOI: 10.1038/s41598-019-54776-w
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 predicts morbidity in adults with Fontan physiology

Abstract: Morbidity in patients with single-ventricle Fontan circulation is common and includes arrhythmias, edema, and pulmonary arteriovenous malformations (PAVM) among others. We sought to identify biomarkers that may predict such complications. Twenty-five patients with Fontan physiology and 12 control patients with atrial septal defects (ASD) that underwent cardiac catheterization were included. Plasma was collected from the hepatic vein and superior vena cava and underwent protein profiling for a panel of 20 analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…We found no within-subject differences in plasma concentrations of BMP9 GFD, BMP10 proprotein, or BMP9/10 GFD across different sampling sites, in agreement with a recent report regarding BMP9 GFD (11) and failing to support the idea that ALK1 ligands are the “hepatic factor” required to prevent PAVMs. However, it remains possible that liver-derived BMP9 or BMP9/10 proproteins (not assayed) may exhibit site-dependent concentration differences, or that enzymes required to cleave proproteins are unavailable in the Glenn circulation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found no within-subject differences in plasma concentrations of BMP9 GFD, BMP10 proprotein, or BMP9/10 GFD across different sampling sites, in agreement with a recent report regarding BMP9 GFD (11) and failing to support the idea that ALK1 ligands are the “hepatic factor” required to prevent PAVMs. However, it remains possible that liver-derived BMP9 or BMP9/10 proproteins (not assayed) may exhibit site-dependent concentration differences, or that enzymes required to cleave proproteins are unavailable in the Glenn circulation.…”
Section: Discussionsupporting
confidence: 88%
“…Diagnoses in 38 controls [mean age 5.8 years (4 months - 12.6 years); 21 males, 17 females] included: small shunt lesions (21), repaired forms of congenital heart disease with two-ventricle physiology (11), vascular stenosis (5), valvar obstructive lesions (2), and hypertrophic cardiomyopathy (1). Primary cardiac diagnoses in 9 Glenn cases [mean age 2.9 years (range 22 months to 5.1 years); 7 males, 2 females] included: variants of hypoplastic left heart syndrome (5); pulmonary atresia with intact ventricular septum (2); double outlet right ventricle with pulmonary atresia (1); and heterotaxy with right atrial isomerism (1).…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these data further support that sVEGFR1 may have a role in PAVM pathophysiology given that sVEGFR1 sequesters VEGF-A to decrease VEGF-A bioavailability and signaling. Two recent studies have also reported that Angiopoietin-2 is elevated in patients with palliated univentricular CHD compared to patients with biventricular CHD (6,29). Angiopoietin-2 is associated with vascular remodeling, but these studies found no difference in ANG-2 levels in HV blood compared to paired SVC blood.…”
Section: Discussionmentioning
confidence: 93%
“…Angiopoietin-2 is associated with vascular remodeling, but these studies found no difference in ANG-2 levels in HV blood compared to paired SVC blood. Shirali et al (6) 1C, Supplementary Table 1), although these data are from a small sample (n = 7). Finally, an important note is that sVEGFR1 was not quantified in either of these recent studies.…”
Section: Discussionmentioning
confidence: 97%
“…22 Angiopoietin-2 levels were shown to be associated with the burden of atrial arrhythmias. 23 Faecal calprotectin levels may be able to detect the development of protein losing enteropathy in Fontan patients; however, one should strive for earlier identification of Fontan failure as the disease process is difficult to reverse at this stage. 24 Overall, the Fontan circulation is characterised by complex interactions between multiple organ systems with continuous interplay among the heart, lungs, liver, kidneys, and vasculature.…”
Section: Discussionmentioning
confidence: 99%